2019
DOI: 10.1136/bjophthalmol-2018-313498
|View full text |Cite
|
Sign up to set email alerts
|

Two-year observation of posterior corneal elevations after small incision lenticule extraction (SMILE) for myopia higher than −10 dioptres

Abstract: AimTo investigate the change in posterior corneal elevations (PCEs) of eyes with extremely high myopia 2 years after small incision lenticule extraction (SMILE).MethodsWe evaluated 39 eyes of 39 patients with spherical equivalent higher than −10.00 dioptres (D). Using a Scheimpflug camera (Pentacam), we measured change in PCEs at 1 day, 3 months, 6 months and 2 years after SMILE. Another 34 eyes of 34 patients who underwent femtosecond laser-assisted in situ keratomileusis (FS-LASIK) were examined before, at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 35 publications
8
28
2
Order By: Relevance
“…We found Change in PCE has statistical significance only at long term follow-ups, there was no significant difference between the two groups at 3-or 6-months post operation. Many studies [2,14,19] have reported similar results and provide complementary evidence for high myopia. Although the FS-LASIK procedure has been optimized by the femtosecond laser in past 10 years, complications relating to the corneal flap still occur in an otherwise perfect FS-LASIK [25] .…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…We found Change in PCE has statistical significance only at long term follow-ups, there was no significant difference between the two groups at 3-or 6-months post operation. Many studies [2,14,19] have reported similar results and provide complementary evidence for high myopia. Although the FS-LASIK procedure has been optimized by the femtosecond laser in past 10 years, complications relating to the corneal flap still occur in an otherwise perfect FS-LASIK [25] .…”
Section: Discussionmentioning
confidence: 67%
“…Guofu Chen [ Cylinder :-0.66±0.7 0 (≥−6.00) Yueming Zhou [18] 2016 CT Chinese 66 7.58±2.14 (-6.125 ~ -9.75) Xueyi Zhou [19] 2019 CT English 39 −10.79±0.81 (-10.00~−13.00)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations